Quantum mechanics of minds and worlds - Barrett, Jeffrey Alan (Oxford Oxford University Press, 1999)
The standard theory of quantum mechanics is in one sense the most successful physical theory ever predicting the behavior of the basic constituents of all physical things. No other theory has ever made such accurate empirical predictions.the most notable
Keywords: Quantum theory; Physical measurement